An Agency Approach to Local Authorities' Behaviour - Ana Bravo; Antonio Silvestre (European Regional Science Association (ERSA), 2006)
This paper aims at presenting a simple model of local decision-making based on the hypothesis of monopoly power on the part of local governments. It adds the contribution of the principal-agent theory by assuming that: (a) monopolistic behavior is constrained by voters' efforts to monitor the outcomes of policies; (b) local governments' policies affect local property values. Given those assumptions, the degree of capitalization of property taxes is shown to determine the incentive for voters' control over policies' outcomes.
Keywords: 330